Can Australia Reach the World Health Organization Hepatitis C Elimination Goal by 2025 Among Human Immunodeficiency Virus–positive Gay and Bisexual Men?. (28th February 2019) - Boettiger, David C; Salazar-Vizcaya, Luisa; Dore, Gregory J; Gray, Richard T; Law, Matthew G; Callander, Denton; Lea, Toby; Rauch, Andri; Matthews, Gail V
Abstract: Background: Human immunodeficiency virus (HIV)–positive gay and bisexual men (GBM) in Australia are well engaged in care. The World Health Organization's (WHO) hepatitis C virus (HCV) elimination target of an 80% reduction in incidence by 2030 may be reachable ahead of time in this population. Methods: We predicted the effect of treatment and behavioral changes on HCV incidence among HIV-positive GBM up to 2025 using a HCV transmission model parameterized with Australian data. We assessed the impact of changes in behavior that facilitate HCV transmission in the context of different rates of direct-acting antiviral (DAA) use. Results: HCV incidence in our model increased from 0.7 per 100 person-years in 2000 to 2.5 per 100 person-years in 2016 and had the same trajectory as previously reported clinical data. If the proportion of eligible (HCV RNA positive) patients using DAAs stays at 65% per year between 2016 and 2025, with high-risk sexual behavior and injecting drug use remaining at current levels, HCV incidence would drop to 0.4 per 100 person-years (85% decline from 2016). In the same treatment scenario but with substantial increases in risk behavior, HCV incidence would drop to 0.6 per 100 person-years (76% decline). If the proportion of eligible patients using DAAs dropped from 65% per year in 2016 to 20% per year in 2025 and risk behavior did not change, HCV incidence would drop to 0.7 per 100 person-years (70% reduction). Conclusions: Reaching the WHO HCV elimination target by 2025 among HIV-positive GBM in Australia is achievable. Abstract : Hepatitis C virus (HCV) incidence among Australia's human immunodeficiency virus (HIV)–positive gay and bisexual population is likely to decline sharply with direct-acting antiviral use, even with increases in risk behavior. Our model suggests that reaching the World Health Organization HCV elimination target ahead of time among this population is achievable.